Evolución y crisis de la ideología de izquierdas / Mercedes Cabrera, Ramón Cotarelo, Ludolfo Paramio, Miguel Ángel Quintanilla, Ramón Varas Machuca - Cabrera, MercedesCotarelo, Ramón (1943-) Paramio Ludolfo (1948-) Quintanilla, Miguel ÁngelVaras Machuca, Ramón (Nubes y tierra)
En el verso de la portada: Fundación Pablo Iglesias